Holocaust in Lithuania in Four Perspectives (about the Thesis of Stanislovas Stasiulis „The Historiography of the Holocaust in Lithuania: Traditions and Problems“) - Dambrauskas, Audrius (Lietuvos istorijos studijos, 2018)
[text in Lithuanian]
Keywords: none